Algebraic Hyperstructures of Vague Soft Sets Associated with Hyperrings and Hyperideals - Ganeshsree Selvachandran; Abdul Razak Salleh (The Scientific World Journal)
We apply the classical theory of hyperrings to vague soft sets to derive the concepts of vague soft hyperrings, vague soft hyperideals, and vague soft hyperring homomorphism. The properties and structural characteristics of these concepts are also studied and discussed. Furthermore, the relationship between the concepts introduced here and the corresponding concepts in classical hyperring theory and soft hyperring theory is studied and investigated.